Fuentes documentales sobre el colegio Real Ntra. Sra. de Loreto (siglo XVII) - LLERA LLORENTE, María Teresa (Revista General de Información y Documentación, 2009)
This paper presents a study of sources on the Royal School of Our Lady of Loreto during the 17th Century. Not only has a descriptive study about papers kept in the Archive of the Royal Palace been done, but also the contents of some other primary and secondary sources in the National Library of Spain, the Municipal Archive of Madrid Townhall, and the Francisco de Zabálburu Library has been analysed. In addition the Royal Palace Archive´s sources have been studied by different points of view.
Keywords: Specialized Information Sources; Documentation on Arts and Social Sciences; Royal School of Our Lady of Loreto; Royal Palace Archive (Madrid)